2010
DOI: 10.1093/eurheartj/ehp595
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of trabeculated left ventricular mass using cardiac magnetic resonance imaging in the diagnosis of left ventricular non-compaction

Abstract: The method described is reproducible and provides an assessment of the global amount of LV trabeculation. A trabeculated LV mass above 20% of the global LV mass is highly sensitive and specific for the diagnosis of LVNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
301
2
47

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 458 publications
(358 citation statements)
references
References 19 publications
8
301
2
47
Order By: Relevance
“…All ll studies in pediatric patients with NCM have shown higher prevalence of familiar cases, facial dysmorphisms and Wolf Parkinson White syndrome compared with adults in whom the usual findings are secondary arrhythmias, [18][19][20][21][22] as well as more cardiovascular symptoms. NCM may be asymptomatic or it can present with symptoms of severe left ventricular dysfunction, arrhythmias and embolic events [23][24][25]. In a small caseseries, mean time to onset of symptoms after diagnosis was 3 years and 6 months [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All ll studies in pediatric patients with NCM have shown higher prevalence of familiar cases, facial dysmorphisms and Wolf Parkinson White syndrome compared with adults in whom the usual findings are secondary arrhythmias, [18][19][20][21][22] as well as more cardiovascular symptoms. NCM may be asymptomatic or it can present with symptoms of severe left ventricular dysfunction, arrhythmias and embolic events [23][24][25]. In a small caseseries, mean time to onset of symptoms after diagnosis was 3 years and 6 months [5].…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler can identify flow among the intertrabecular recesses [23]. For MRI the diagnostic criterionis that of Petersen et al This is the ratio between the compact and noncompact portion of the myocardium greater than 2.3 measured at the end ofdiastole, which is usually bigger than 2,3 [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac MRI is an emerging modality in the diagnosis of LVNC carrying the advantage of high spatial resolution and image quality [73][74][75] (Figure 3). Three diagnostic criteria have been developed by Petersen et al, Jacquier et al, and Stacey et al (Table 2).…”
Section: Diagnosismentioning
confidence: 99%